Evolution of hole trapping in the oxynitride gate p-MOSFET subjected to negative-bias temperature stressing - Boo, A. A. (2013)
We present experimental evidence of a thermally activated transformation of negative-bias-temperature-stress-induced transient hole trapping at preexisting oxide traps into more permanent trapped holes in the ultrathin oxynitride gate p-MOSFET. The transformation is also shown to correlate with the generation of stress-induced leakage current, indicating that it is one of the key mechanisms of bulk trap generation. A similar observation (reported elsewhere) applies to the HfO2 gate p-MOSFET, implying that the observed hole-trap transformation is a common mechanism for bulk trap generation across different gate oxide technologies. The results further imply that preexisting oxide defects, usually deemed irrelevant to negative-bias temperature instability, have a definite role on long-term device parametric drifts.